2014
DOI: 10.1177/0268355514541981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical prediction scores for the diagnosis of deep vein thrombosis in unselected population of outpatients and inpatients

Abstract: The modified Wells and the Constans score appear to be useful in the unselected population of outpatients and inpatients and particularly in the outpatient subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…The most practical clinical method used to determine the likelihood of DVT is the Wells scoring system (1,(48)(49)(50)(51)(52) The details of this system are presented in Table 2. However, the guidelines and reports in the present articles do not consider the Wells scoring system to be a reliable test for pregnant women.…”
Section: Wells Scoring Systemmentioning
confidence: 99%
“…The most practical clinical method used to determine the likelihood of DVT is the Wells scoring system (1,(48)(49)(50)(51)(52) The details of this system are presented in Table 2. However, the guidelines and reports in the present articles do not consider the Wells scoring system to be a reliable test for pregnant women.…”
Section: Wells Scoring Systemmentioning
confidence: 99%
“…Similar findings have been published by other groups. 18 Sermsathanasawadi et al 72 applied and compared five different clinical scores (Wells, modified Wells, Kahn, St Andre and Constans scores) on 500 consecutive outpatients and inpatients. They showed that modified Wells score and Constans score were more accurate for unselected outpatients and inpatients (based upon AUC-ROC), but they had poor prediction values for inpatients (AUC-ROC: 0.59-0.60).…”
Section: Inpatients Outpatients and Primary Care Patientsmentioning
confidence: 99%
“…Importantly, the detachment of thrombosis can migrate to brain or lung to induce pulmonary thromboembolism or cerebral thromboembolism, which severely threatens patient's life . Though DVT can be diagnosed based on clinical manifestation, such as imaging/lab results and body signs, frequent misdiagnosis in clinics was made since 70%‐80% of DVT patients had no clinical symptoms at early stage due to slow and insidious onset . Veins that recanalize more rapidly have better‐preserved valve integrity and a lower incidence of reflux and patients with shorter recanalization times have been shown to have an improved clinical outcome .…”
Section: Introductionmentioning
confidence: 99%